Pengaruh Internalisasi Nilai Moral Kristiani dalam Pembelajaran Agama Katolik terhadap Pembentukan Karakter Siswa Sekolah Dasar - Maria Yovita Neo (Lembaga Yasin AlSys, 2026)
Amid the various challenges of contemporary development, schools have a strategic responsibility to instill moral values that shape students into individuals who are faithful, responsible, disciplined, and respectful of others. This study aims to analyze the internalization of Christian moral values in Catholic Religious Education and its contribution to the character formation of fifth-grade students at SDK Wolomage. The study employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that Christian moral values were internalized through communal prayer, reflection, group discussions, teacher role modeling, and the habituation of love, honesty, responsibility, and discipline. Most students demonstrated positive character development, as indicated by increased spiritual awareness, respect for teachers, and responsibility in completing school assignments. However, character formation has not been fully optimal because undisciplined behavior, talking during lessons, and teasing among students were still observed. Other constraints included limited instructional time, differences in disciplinary approaches among teachers, low parental involvement, and the influence of the social environment and digital media. This study concludes that the internalization of Christian moral values through learning, role modeling, and habituation contributes to students’ character formation, but its effectiveness requires consistent guidance and collaboration among schools, teachers, and parents. These findings provide practical implications for developing Catholic Religious Education that is more contextual, sustainable, and integrated with school culture and the family environment.